Dampak Penurunan Harga Karet Terhadap Kondisi Ekonomi Petani di Desa Lesung Batu Muda Kecamatan Rawas Ulu Kabupaten Musi Rawas Utara - Rizki Gemala Busyra; Boca Irpanto (Universitas Batangahari Jambi, 2022)
Rubber commodity is one of the plantation commodities which has played an important role for the economy in Indonesia since ancient times. The success of rubber plantations is not only seen from its production and productivity, it can also be seen from the income received by the farmers. The purpose of this study was to describe the income, food consumption, and non-food consumption of rubber farmers before and after the decrease in rubber prices and to analyze the differences in income, food consumption, and non-food consumption of rubber farmers before and after the decrease in rubber prices in Lesung Village. Batu Muda, Rawas Ulu District. The number of samples of farmers in this study were 35 people. Methods of collecting data using the method survey. The results of this study indicate that income, food consumption and non-food consumption of farmers in Lesung Batu Muda Village, Rawas Ulu District, experienced a change of 38.37 into the Good category at the time before the decrease in rubber prices and after the decrease in rubber prices it decreased by 28.26 in. in the Poor category. Based on the results of the Wilcoxon test calculation, Z count (-5.26) < Z table (-1.65) with = 0.05 so Ho is rejected and H1 is accepted. Thus it can be concluded that the decrease in rubber prices has a significant effect on changes in income conditions, food consumption and non-food consumption of farmers in Lesung Batu Muda Village. Keywords: Rubber Price Decrease, Income, Food Consumption, Non-Food Consumption